Serum creatinine to cystatin C ratio is a prognostic indicator in esophageal squamous cell carcinoma receiving neoadjuvant immunochemotherapy - Feng, Jifeng; Wang, Liang; Yang, Xun; Chen, Qixun (Frontiers in Immunology, 2025)
BackgroundThis study aimed to explore the relationship between pretreatment serum creatinine to cystatin C ratio (CCR) and prognosis in patients with esophageal squamous cell carcinoma (ESCC) receiving neoadjuvant immunochemotherapy (NICT).MethodsTwo hundred and two ESCC patients who received NICT were included in the current retrospective study. The restricted cubic spline displayed the non-linear relationship between prognosis and CCR. The association between overall survival (OS)/disease-free survival (DFS) and CCR was also investigated. Kaplan-Meier methods and Cox proportional hazard regression analyses were employed.ResultsThe connection between DFS/OS and CCR suggested that their interaction was non-linear. The restricted cubic spline (RCS) model identified 97.5 as the ideal cutoff point for CCR and divided it into 2 groups. Patients exhibiting low CCR demonstrated significantly worse 3-year DFS (48.5% vs. 74.3%, P<0.001) and OS (62.9% vs. 82.9%, P=0.001) compared to those with high CCR. The results indicated that CCR had prognostic significance for the ESCC cases stratified according to subgroup analyses. Compared to the low CCR group, subsequent multivariate analysis revealed that the high CCR group reduced the risk of recurrence by 56.0% (P=0.001) and the risk of death by 51.8% (P=0.013), respectively.ConclusionThe therapeutic efficacy of NICT for ESCC can be predicted by pretreatment CCR. Although the CCR may not have attained a very high quality, it still holds certain significance for clinical practice in ESCC patients undergoing NICT.